1977
DOI: 10.1002/1097-0142(197705)39:5<2231::aid-cncr2820390541>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal bone cysts.A clinicopathological study of 105 cases

Abstract: A clinicopathological review of 105 cases of aneurysmal bone cyst is reported. Age and sex distribution and localization were in agreement with two previously reported large series. Recurrence occurred in 30.5% of all the cases and in 34.2% of those treated by curettage. Proved incompleteness of surgical removal was an important factor in recurrence (12 out of 17 cases or 70.6%). The recurrence rate was significantly (P2 less than 0.01) higher in cases with a mitotic index of seven or more per 50 fields (X 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
1
11

Year Published

1979
1979
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(126 citation statements)
references
References 17 publications
3
111
1
11
Order By: Relevance
“…Pathological material was obtained at the time of attempted surgical excision in six cases (patients 1, 3,5,7,12,13), and after surgical biopsy because of atypical radiological presentation in three cases (patients 8,11,14). According to pathology, one ABC was associated with ossifying fibromas (patient 7) and one with a unicameral bone cyst (patient 12).…”
Section: Methodsmentioning
confidence: 99%
“…Pathological material was obtained at the time of attempted surgical excision in six cases (patients 1, 3,5,7,12,13), and after surgical biopsy because of atypical radiological presentation in three cases (patients 8,11,14). According to pathology, one ABC was associated with ossifying fibromas (patient 7) and one with a unicameral bone cyst (patient 12).…”
Section: Methodsmentioning
confidence: 99%
“…Although the incidence of ABC is reported to be only 0.14 per 100.000 (2), since 1966, nearly 1000 articles have been published on this topic. The nature of ABC, however, has still remained unclear and controversial (3)(4)(5)(6)(7)(8), even leading Vicenzi to the conclusion that none of the present etiopathogenic theories is based on objective and convincing data (9). Most recently, Sciot et al reported chromosomal aberrations in ABC suggesting that at least some ABCs are true neoplasms (10).…”
mentioning
confidence: 99%
“…[1 ]. There is general agreement that the aneurysmal bone cyst is a benign, nonneoplastic disorder, although the exact pathogenesis and cause continue to be debated.…”
mentioning
confidence: 99%